Platelet rich plasma for the treatment of osteoarthrosis knee - Maheshwari, Prashant; Harshwardhan, Hemeshwar (International Journal of Research in Orthopaedics, 2017)
Background: New studies focused on modern therapeutic methods which stimulate cartilage healing and repair the damage, including the use of platelet-rich plasma (PRP) as a cocktail of growth factors. This study has the purpose to present the use of PRP in management of knee osteoarthrosis and its outcomes up to 6 month follow up. Methods: 58 patients with 100 knees (32 male, 26 female) with Kellgren Lawrence grade 1, 2,3 and 4, aged between 50 to 65 years between February 2015 to December 2015 treated with 4 ml of intra-articular PRP injections at 4 week interval in each affected knee and evaluated using WOMAC and VAS scores before injection and on follow up at end of the 1st, 3rd, and 6th month. Results: The mean age was 58.29 years. Improvement in WOMAC score for KL grade 1 (32.61%), grade 2 (31.12%), grade 3(26.54%) whereas only 13.68% in KL grade 4 at end of 6month follow up. Improvement in VAS score for KL grade 1 (41.30%), grade 2 (38.02%), grade 3 (47.68) whereas only 12.74% in grade 4 at the end of 6 month follow up. Results show statistically higher significant improvement seen in WOMAC and VAS for KL grade 1, 2, and 3 as compared to grade 4 at 6 months follow up. Conclusions: The results of our study illustrated that the treatment with intra articular PRP injections is safe and effective in reducing pain and stiffness as well as improve knee function and quality of life in early stages of knee osteoarthrosis.